Multi-objective decoupling control strategy for low voltage ride through under asymmetrical faults - LIU Qinyi; ZHONG Qidi; WANG Shiwen; LU Yajun; SUN Jinping; LIU Fei (电力工程技术, 2024)
For the traditional low voltage ride through control under asymmetrical faults, due to the limited control degrees of freedom, the grid-connected inverter control suffers from the problem of not being able to simultaneously realize the output current negative-sequence component suppression and the DC side voltage double-frequency fluctuation suppression. In this regard, a multiple-objective decoupling control strategy is proposed for low voltage ride through of two-stage grid-connected photovoltaic system under asymmetrical faults. The strategy sets the control objective of the inverter as the negative-sequence component suppression of the output current and gives a reference value calculation method for the inner current loop considering the inverter output current limit and reactive power output demand. The super-capacitor is connected to both ends of the DC bus capacitor through the bidirectional Buck-Boost converter to maintain its voltage stability, and the DC side voltage double-frequency fluctuation is transferred to the super-capacitor side. The simulation results show that under the proposed control strategy, the unbalance between three phases of the inverter is reduced and the output current distortion is improved. The double frequency fluctuation of the DC side voltage is reduced significantly compared with the traditional control method.